Meaning Equivalence in Pegon Translation of Lubabul Ḥadith: Analysis Based on Mashadi Said’s Translation Theory - Ahmad Baihaqi; Khairul Muttaqin (JURNAL ISLAM NUSANTARA, 2025)
This study aims to examine the quality of meaning equivalence in Pegon translations of Lubabul Ḥadis by Jalaluddīn al-Suyuṭi using Mashadi Saʿid’s translation framework. Pegon has historically functioned as an essential medium of Islamic literacy in Javanese pesantren, enabling access to Arabic religious texts through localized translation. However, previous studies indicate that lexical archaism, literal translation strategies, and socio-linguistic change have reduced Pegon’s semantic accessibility for contemporary santri. This research employs a qualitative library research design based on close reading and comparative textual analysis of Arabic and Pegon texts. Data were analyzed using Mashadi Saʿid’s criteria of accuracy, clarity, naturalness, and dynamic equivalence. The findings show that Pegon originally functioned as an epistemic and pedagogical bridge but is increasingly weakened by obsolete vocabulary. Pegon translations largely maintain semantic accuracy but often lack clarity and naturalness due to rigid Arabic syntactic calques. In addition, socio-cultural and generational shifts reduce the ethical and communicative impact of Pegon-translated hadith teachings. This study contributes to Islamic philology by integrating modern translation theory into Pegon studies and highlights translation quality as a key issue in pesantren literacy. It recommends adaptive strategies such as contextual glossaries and annotated translations to revitalize Pegon’s pedagogical relevance.